Physical activity profiles and selected muscular fitness variables in English schoolchildren: A north–south divide?. Issue 8 (16th November 2016) - Ingle, Lee; Stephenson, Ashlie; Sandercock, Gavin R.
Abstract: The aim of the study was to compare and contrast habitual physical activity (PA) profiles and muscular fitness in schoolchildren from northern and southern regions of England. Data were collected from two secondary schools in the north east (NE) of England. The study procedures followed methods employed by the East of England Healthy Hearts Study in 10–16-year-old boys and girls based in the south east (SE) region of England and data were compared. Habitual physical activity (PAQ-A), vertical jump test, and hand-grip (HG) strength were assessed. We converted raw scores from all assessments to age- and sex-normalised z -scores. We recruited 597 children (58% boys) in the NE and compared findings to 597 age- and sex-matched boys and girls from the SE. Boys in the SE had significantly stronger HG scores, jumped higher, were more powerful (mean peak power: 2131 W vs. 1782 W; P < 0.0001), and reported being more physically active (mean PAQ-A: 2.9 vs. 2.5; P < 0.0001) than their male counterparts in the NE. In girls, the opposite trend was evident. Girls from the NE of England had a higher HG score, jumped higher, and were more powerful (mean peak power: 2114 W vs. 1839 W; P < .0001) than their peers from the SE. Regional variations in the habitual PA profiles and muscular fitness of schoolchildren from the SE and NE of England do exist. The systematic surveillance of children's PA and fitness profiles throughout England would help identify regional inequalities on a larger scale.